The Dato Yuthitham and the administration of Islamic law in southern Thailand - Wan Muhammad, Ramizah (University of Melbourne, 2011)
This paper discussed about the administation of islamic law particularly on datok yuthitham as a shariah court judge and his jurisdiction to hear cases.